Failure monitoring system of a traffic light - Che Soh, Azura; Mohd Noor, Samsul Bahari; Wagiran, Rahman; Sulaiman, Nasri; Mohd Sidek, Roslina (Universiti Putra Malaysia Press, 2002)
This paper presents the design and development of a system to monitor the failure of a traffic light operation as a continuation to failure detection system developed [6]. The heart of the system is an 8-bit PICI6F84, which will run on pre-programmed instructions. The failure signal from the traffic light has been fed to microcontroller on-board system via appropriate interfacing devices. This monitoring system will automatically send a signal to display on panel system in the control room whenever there is a faulty condition occurs in the traffic light.